Deformed wing virus can be transmitted during natural mating in honey bees and infect the queens - Amiri, Esmaeil (Sci Rep, 2016)
Deformed wing virus is an important contributor to honey bee colony losses. Frequently queen failure is reported as a cause for colony loss. Here we examine whether sexual transmission during multiple matings of queens is a possible way of virus infection in queens. In an environment with high prevalence of deformed wing virus, queens (n = 30) were trapped upon their return from natural mating flights. The last drone’s endophallus (n = 29), if present, was removed from the mated queens for deformed wing virus quantification, leading to the detection of high-level infection in 3 endophalli. After oviposition, viral quantification revealed that seven of the 30 queens had high-level deformed wing virus infections, in all tissues, including the semen stored in the spermathecae. Two groups of either unmated queens (n = 8) with induced egg laying, or queens (n = 12) mated in isolation with drones showing comparatively low deformed wing virus infections served as control. None of the control queens exhibited high-level viral infections. Our results demonstrate that deformed wing virus infected drones are competitive to mate and able to transmit the virus along with semen, which occasionally leads to queen infections. Virus transmission to queens during mating may be common and can contribute noticeably to queen failure.